Design and development of Innovative Quality Function Deployment model. (14th January 2008) - Sankaran, R.A.; Senthil, V.; Devadasan, S.R.; Pramod, V.R.
After the Second World War, companies adopted Total Quality Management (TQM) to keep pace with the global competition. One of the cornerstones of TQM is customer voice adoption. This task is facilitated using the technique called Quality Function Deployment (QFD). Meanwhile, the contemporary researchers have pointed out that attaining high degrees of quality has to be accompanied by innovative strategies for achieving core competencies by the modern organisations. In order to fulfil this need, this paper proposes a technique under the name, 'Innovative Quality Function Deployment' (IQFD). This technique has been designed by blending QFD and Innovation Management (IM) principles. The practical feasibility of implementing IQFD was examined in an Indian Gear motor manufacturing company. The experiences gained through this examination were used to design a systematic procedure for successfully implementing IQFD in practical arena.